Growth, modernization and management of new villages and their community in Malaysia - Wee, Jeck Seng; Phang, Siew Nooi; Khalil, Samihah (IJSSER, 2018)
The existence of New Villages (NVs) in Malaysia since the end of the Second World War and the government’s lack of clear guidelines as to their growth and development has resulted in many of the NVs to be in a state of limbo at present. The gravity of this dilemma has not been lost on both the policy makers at the centre and the NV communities themselves. In the past many decisions regarding the NVs has followed the elite theory where policies concerning the NVs are made based on class divisions within the NVs and the supra government. The elites comprising the government authorities and the village leaders are responsible for all matters and activities relating to the overall development of the NVs. As time progresses and with the influence of technology, coupled with better educated residents and effects of globalisation, these factors began to impact on the community in the NVs. The modernisation theory signalled the start of the new order in the NVs and there began a change in the political, social and economic fabrics of the NV community. Physically, the NVs changed from its origins as a temporary resettlement village in the outskirts to a permanent housing settlement in and within the periphery of an urban setting. This influenced the political and economic behavior of the NV community as evidenced in the voting trends in recent elections and types of economic development taking place in the NVs. These changes demonstrate a shift away from the elite system of only “leaders” who will decide for the NVs to a NV community that wants to speak out and be heard. The NVs of Malaysia is an example of how modern society wants to move away from a hierarchical social order typical of the past and challenges the notion that a typical elite or top-down bureaucratic structure to policy making is unquestionable. This paper aims to examine the modernisation theory in policy making and governance of communities in Malaysia.